Genome wide association study of chronic traumatic encephalopathy: Genetics/genetic factors of non‐Alzheimer's tauopathies. (7th December 2020) - Atherton, Kathryn; Khan, Mohammed Muzamil; Shea, Conor; Chung, Jaeyoon; Nair, Evan; Baucom, Zachary H.; Abdolmohammadi, Bobak; Uretsky, Madeline; Martin, Brett M.; Palmisano, Joseph; Farrell, Kurt W.; Cherry, Jonathan D.; et al.
Abstract: Background: Chronic traumatic encephalopathy (CTE) is a neurodegenerative disease associated with exposure to repetitive head impacts (RHI). CTE has distinct neuropathology defined by perivascular hyperphosphorylated tau (ptau) deposition. The presence and severity of CTE pathology varies among those with similar RHI exposure, suggesting a role for non‐RHI risk factors, including genetics. Here we conducted the first genome‐wide association study (GWAS) of neuropathologically‐confirmed CTE. Method: 175 brain donors from the Veterans Affairs‐Boston University‐Concussion Legacy Foundation Brain Bank with known exposure to RHI in the form of contact sports and/or military service were assessed for CTE pathology. CTE pathology was staged on a semiquantitative scale from 0 to 4 (0 = absent; 4 = most severe). Ptau burden was also assessed across 11 brain regions commonly affected in CTE on a semiquantitative scale from 0 to 3 (0 = absent; 3 = most severe). We tested the association of genome‐wide genotyped and imputed single nucleotide polymorphisms (SNPs) with CTE stage in a linear regression model adjusted for 10 principal components of population substructure. We tested the association of top hits with ptau burden in each of the 11 brain regions. Result: Two loci achieved genome‐wide significance: top SNP rs63565460 [minor allele frequency (MAF) = 0.08; beta = ‐1.64; p = 2.4 × 10 −8 ] is an intronic SNP in PIP5K1B on chromosome 9; and top SNP rs12447028 (MAF = 0.07; beta = ‐1.84, p = 2.6 × 10 −8 ) is an intronic SNP in ABAT on chromosome 16. The PIP5K1B locus had the largest effects in cortical regions. PIP5K1B is expressed in brain and has been associated with intelligence in GWAS. The ABAT locus had the largest effects in the inferior orbital gyrus and the locus coeruleus. ABAT is expressed in brain and has been associated in GWAS with anger proclivity, a symptom of CTE. The ABAT protein functions in GABA catabolism. Conclusion: In the first GWAS of CTE, two promising loci in PIP5K1B and ABAT achieved genome‐wide significance. Both loci had the largest effects in brain regions affected early in CTE. Efforts to enlarge the sample size, incorporate measures of RHI exposure and test additional endophenotypes are underway. Identified loci may implicate disease mechanisms, provide targets for therapies, and guide counseling of athletes regarding risk of play.